2024
DOI: 10.1038/s41594-024-01239-0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome-bound NR5A2 structure reveals pioneer factor mechanism by DNA minor groove anchor competition

Wataru Kobayashi,
Anna H. Sappler,
Daniel Bollschweiler
et al.

Abstract: Gene expression during natural and induced reprogramming is controlled by pioneer transcription factors that initiate transcription from closed chromatin. Nr5a2 is a key pioneer factor that regulates zygotic genome activation in totipotent embryos, pluripotency in embryonic stem cells and metabolism in adult tissues, but the mechanism of its pioneer activity remains poorly understood. Here, we present a cryo-electron microscopy structure of human NR5A2 bound to a nucleosome. The structure shows that the conser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Collectively, the combination of genome-wide binding profiles, chromatin accessibility assays and in vitro nucleosome binding has proven that Nr5a2 exhibits properties consistent with pioneer transcription factors [ 21 ]. Recently, Kobayashi et al further demonstrated the mechanism underlying how Nr5a2 engages with nucleosomes to exert its pioneer activity [ 58 ]. The crystallographic analysis of the human NR5A2-DNA complex revealed that the α-helix of the zinc finger domain binds to the major groove, while the CTE (carboxy-terminal extension) binds to the minor groove [ 59 ].…”
Section: The Role Of Nr5a2 In Zgamentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the combination of genome-wide binding profiles, chromatin accessibility assays and in vitro nucleosome binding has proven that Nr5a2 exhibits properties consistent with pioneer transcription factors [ 21 ]. Recently, Kobayashi et al further demonstrated the mechanism underlying how Nr5a2 engages with nucleosomes to exert its pioneer activity [ 58 ]. The crystallographic analysis of the human NR5A2-DNA complex revealed that the α-helix of the zinc finger domain binds to the major groove, while the CTE (carboxy-terminal extension) binds to the minor groove [ 59 ].…”
Section: The Role Of Nr5a2 In Zgamentioning
confidence: 99%
“…Nr5a2, acting as a monomer, specifically binds to the DNA motif on both naked DNA and nucleosomes [ 21 , 60 ]. Through presenting a cryo-electron microscopy structure of human NR5A2 bound to a nucleosome, Kobayashi et al observed the CTE loop of the NR5A2 DNA-binding domain interacts competitively with a DNA minor groove anchor of the nucleosome, facilitating the release of entry–exit site DNA, corresponding to the model in which histone–DNA interactions are compensated with pioneer transcription factor–DNA interactions [ 58 , 61 ]. Additionally, while the D159 residue of the CTE is not essential for DNA binding, it is crucial for maintaining stable nucleosome association and continuous DNA “unwrapping” [ 61 ].…”
Section: The Role Of Nr5a2 In Zgamentioning
confidence: 99%